2014
DOI: 10.1007/s10021-014-9812-2
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater Infrastructure Controls Runoff and Dissolved Material Export from Arid Urban Watersheds

Abstract: . (2015) 'Stormwater infrastructure controls runo and dissolved material export from arid urban watersheds.', Ecosystems., 18 (1). pp. 62-75. Further information on publisher's website:http://dx.doi.org/10.1007/s10021-014-9812-2Publisher's copyright statement:The nal publication is available at Springer via http://dx.doi.org/10.1007/s10021-014-9812-2.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 49 publications
2
69
0
Order By: Relevance
“…Runoff coefficients in these study watersheds, in turn, were strongly and negatively related to retention basin density and watershed area and positively related to impervious cover and precipitation. 26 In these watersheds, therefore, retention basin density was associated with increased DIN retention at the watershed scale, whereas the imperviousness and precipitation was associated with decreased DIN retention at the watershed scale. Larger watersheds also had lower runoff coefficients and therefore retained more DIN, as noted by Lewis and Grimm.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Runoff coefficients in these study watersheds, in turn, were strongly and negatively related to retention basin density and watershed area and positively related to impervious cover and precipitation. 26 In these watersheds, therefore, retention basin density was associated with increased DIN retention at the watershed scale, whereas the imperviousness and precipitation was associated with decreased DIN retention at the watershed scale. Larger watersheds also had lower runoff coefficients and therefore retained more DIN, as noted by Lewis and Grimm.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…The results of this study have significant implications for stormwater management in arid cities. Larson and Grimm 35 reported high rates of potential denitrification in stormwater retention basins in the Phoenix area, and Hale et al 26 reported that N delivery was negatively related to the density of retention basins in a watershed. However, our isotopic results suggest that, even though retention basins change the isotopic composition of NO 3 − in stormwater, the mechanisms driving N retention at the scale of rainfall-runoff events are primarily hydrologic, not biogeochemical.…”
Section: Microbially Nitrified Nomentioning
confidence: 99%
See 2 more Smart Citations
“…Urbanization has tremendous consequences for hydrological processes through the alteration of land cover [1], burial of streams [2], creation and destruction of lakes [3], re-plumbing of watersheds with stormwater infrastructure [4,5], and restoration and redesign of streams [6]. Depending on design, stormwater infrastructure can exacerbate or mitigate the effects of urbanization on the transport of water, nutrients, and other pollutants from urban watersheds [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%